Features of use natural lead at production of pogonazhnikh of elements - Koval, Lyubomyr (Forestry, Forest, Paper and Woodworking Industry, 2024)
Factors which hinder to the use natural lead in the process of production of pogonazhnikh elements and their influence on quality of the prepared products are considered. With growth of standard of living users become all more demanding to quality and original appearance of furniture and joiner's wares. Often their constituents are pogonazhni wares the assortment of which at the market of Ukraine is wide enough. If to take a more or less well-to-do user, then at the choice of furniture or joiner's wares it will give advantage to those which after original appearance remind natural material – wood. In the 60-kh years of XX age together with creation of kleiv-rozplavi for revetment of furniture details and development the German firm Adolf Friz equipment for the pack of type pogonazhnikh elements different synthetic materials was the created technology of pack of type pogonazhu by lamination material is a pack (muffling). Quality of pack of pogonazhu natural lead depends on many factors basic from which is: thickness lead; breed of wood from which it is made leads; kind lead; humidity lead; speed of serve in the process of pack; complication of type (size of radiuses of rounding); type of in-use glue.